LEIFMCY: Deployment of an Efficient Low-Cost & Energy-Aware Multiparametric IoT-Based Fertilization and Irrigation Monitoring Model for Cotton Yield Analysis - Ambade , Swapnil Dhanraj; Mishra, Ravi (International Journal of Intelligent Systems and Applications in Engineering, 2023)
With the increasing demands on global agriculture, there is an imperative need to optimize crop yields and promote sustainable agricultural practices. Real-time monitoring and accurate predictions of soil health and crop yields have significant implications for farmers, agronomists, and policymakers. While existing soil analysis models offer certain predictive capabilities, their efficiency is often hindered by issues related to energy consumption, prediction delay, and accuracy levels. Contemporary soil models primarily fall short in addressing the multifaceted nature of soil attributes and their dynamic interactions. These models also struggle to provide real-time insights, frequently leading to delayed interventions, misallocated resources, and suboptimal yields. In this paper, we introduce an advanced, low-cost, and energy-aware multiparametric IoT-based soil analysis model designed to overcome the prevailing limitations. Our system harnesses the synergy of N, P, K, Humidity, and Temperature sensors, augmented with temporal datasets to offer a comprehensive view of the soil's current state. At the core of our analysis, an ensemble learning model combines the strengths of Naive Bayes, Logistic Regression, SVM, MLP, and 1D CNN methods, streamlining accurate yield level predictions. To further refine the model's efficiency, a Q Learning approach is integrated, ensuring both energy conservation and heightened prediction accuracy. When deployed in various agronomic scenarios, the proposed model manifested a marked improvement in prediction metrics. Notably, we observed a 10.5% enhancement in precision, 9.4% in accuracy, 8.5% in recall, and 4.5% in AUC. Moreover, the model reduced the prediction delay by 9.5% compared to its counterparts. These advancements underscore the potential of our model to revolutionize soil analysis techniques, paving the way for smarter, energy-efficient, and productive agricultural practices.